SISTEM PENDUKUNG KEPUTUSAN PENGANGKATAN KARYAWAN TRAINING MENJADI KARYAWAN TETAP BERBASIS WEB DENGAN MENGGUNAKAN METODE SAW - Sitorus P, Forlediska Amelia; Handoko, Widiyanto Tri (LPPM Institut Teknologi Bisnis Dan Bahasa Dian Cipta Cendikia, 2023)
An institution or an office definitely needs personnel or Human Resources (HR). If HR can be well organized, it is hoped that the company can also manage all business processes properly. Every company has criteria for assessing the performance of its employees. Therefore a decision support system was built using the SAW method. By using the SAW method, the best alternative is sought based on the specified criteria. In this study, the SAW method was adopted and can be carried out according to the expected results. Tests in this study used white box and black box testing with the results according to the original plan and can be said to be successful.